Preparation of nitrogen-doped porous carbon-loaded metal oxide and application thereof in rosin esterification
The preparation of nitrogen-doped porous carbon-supported metal oxide catalysts through ball milling assisted strategies has solved the complex operation and low performance of the heterogeneous metal oxide catalyst in the rosin esterification reaction, and achieved efficient catalytic esterification of rosin and polyols The reaction improves the stability and active sites of the catalyst, simplifies the preparation process and reduces costs.
Patent Information
- Application Number
- CN202411378536.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The application of existing heterogeneous metal oxide catalysts in rosin esterification reactions has problems such as complex operational processes, high raw material costs and low catalyst performance, especially in the uneven dispersion of metal oxides during the pyrolysis process, resulting in a reduced catalytic performance.
Using ball mill auxiliary strategy, plant materials, melamine and metal salts are mixed for pyrolysis and carbonization to form a nitrogen-doped porous carbon-supported metal oxide catalyst, which promotes in-situ generation and uniformity of metal oxides through strong hydrogen bonding and coordination. Dispersion, using the synergistic effect of nitrogen doping and metal oxide to improve catalytic performance.
It realizes efficient catalyzing of the esterification reaction between rosin and polyol at lower temperatures and short time, improves the active site and stability of the catalyst, simplifies the preparation process, avoids solvent removal and waste liquid generation, and reduces production. cost.
Smart Images

Figure CN119215956A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon-based catalysts, and in particular relates to the preparation of nitrogen-doped porous carbon-supported metal oxides and the application of the nitrogen-doped porous carbon in rosin esterification. Background Art
[0002] With the increasing emphasis on sustainable development, the synthesis of biomass-derived chemicals has received widespread attention from academia and industry. my country is rich in pine forest resources, and rosin has become a promising natural resin to replace petroleum-based resins due to its renewable and easy processing characteristics. However, the inherent characteristics of rosin, such as low stability and high acid value, limit its wider industrial application. Esterification of the carboxyl groups in the rosin structure has been proven to be an effective rosin modification strategy. The obtained rosin ester derivatives have lower acid values and higher stability, thereby expanding their potential applications in adhesives, printing inks, rubber, coatings and other industries. Due to the low reactivity of the carboxyl group of rosin, the direct esterification reaction of rosin with alcohol often requires a catalyst.
[0003] Traditional homogeneous acid and base catalysts, such as sulfuric acid, phosphoric acid and calcium hydroxide, have been used for the esterification of rosin, but they have problems such as harsh reaction conditions, easy corrosion of equipment, and catalyst recovery. In order to overcome these problems, the development of efficient heterogeneous catalysts has become the focus of rosin esterification research. Recent studies have shown that heterogeneous metal oxide catalysts have good application potential in catalyzing rosin esterification reactions. However, the preparation of heterogeneous metal oxide catalysts at this stage often requires complex operation processes and high raw material costs. At the same time, the catalysts prepared directly using metal oxides have low specific surface areas, and metal oxides are easy to agglomerate, reducing the number of accessible active sites. Therefore, the introduction of suitable carriers to disperse metal oxides is conducive to fully exposing active sites, reducing the agglomeration of metal oxides, and thus improving catalytic performance. Porous carbon is a good carrier for loading metal oxides due to its porous structure. Currently, the commonly used methods for preparing porous carbon loaded with metal oxides include impregnation and coprecipitation. These traditional methods have complex preparation processes and involve time-consuming steps such as solvent removal and aging. During the drying process, metal deposition is easily caused, resulting in uneven dispersion of metal oxides after pyrolysis, and reduced catalyst performance.
[0004] To this end, the present invention adopts a ball milling-assisted strategy, using renewable plant materials as precursors and melamine as a nitrogen doping agent, and the ball milling process is used to enhance the interaction between the plant materials, the nitrogen doping agent and the metal salt to form a highly active surface, thereby facilitating the in-situ generation and uniform dispersion of metal oxides and nitrogen doping during the pyrolysis process. The preparation process of the present invention is simple, does not require the removal of solvents, does not generate waste liquid, is easy to scale up production, and because the doped nitrogen and metal oxides have a synergistic effect, the catalytic performance and stability of the nitrogen-doped porous carbon-supported metal oxide catalyst can be significantly improved, so that the prepared nitrogen-doped porous carbon-supported metal oxide can catalyze the esterification reaction of rosin with a variety of polyols at a lower temperature and a shorter reaction time. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a nitrogen-doped porous carbon-supported metal oxide and its application in rosin esterification.
[0006] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a nitrogen-doped porous carbon-supported metal oxide comprises the following steps: (1) ball-milling and mixing plant materials, melamine and metal salt; (2) The mixture obtained in step (1) is subjected to pyrolysis and carbonization in a nitrogen atmosphere to obtain the nitrogen-doped porous carbon-supported metal oxide.
[0007] Furthermore, the mass ratio of the plant material, melamine and metal salt used in step (1) is 10:1.25:(3.75-37.5), preferably 10:1.25:(3.75-7.5).
[0008] Furthermore, the plant material includes one or more of fir sawdust, hemp stalks and the like.
[0009] Furthermore, the metal salt includes nitrate, acetate or chloride of one or more metals such as magnesium, zinc, cerium, zirconium, etc.
[0010] Furthermore, the ball milling speed in step (1) is 100-800 r / min, preferably 200-600 r / min; the time is 2-10 h, preferably 2-6 h.
[0011] Furthermore, the heating rate of the pyrolysis carbonization in step (2) is 5-15°C / min, preferably 5-8°C / min; the temperature is 500-800°C, preferably 500-700°C; and the time is 1-4 h, preferably 2-3 h.
[0012] The nitrogen-doped porous carbon-supported metal oxide prepared by the above method can be used to catalyze the esterification reaction of rosin.
[0013] Furthermore, the nitrogen-doped porous carbon-supported metal oxide is used as a catalyst to catalyze the esterification reaction of rosin and polyol to obtain the corresponding rosin ester.
[0014] Furthermore, the polyol includes one or more of glycerol, ethylene glycol, polyethylene glycol, and pentaerythritol.
[0015] Furthermore, the mass ratio of rosin to polyol is 15:(1.5-4.6); preferably 15:3.2.
[0016] Furthermore, the esterification reaction temperature is 210-250°C, preferably 230°C; the time is 2-6 h, preferably 4 h.
[0017] The significant advantages of the present invention are: (1) The present invention starts from plant materials and uses a simple ball milling-assisted strategy to prepare nitrogen-doped porous carbon-supported metal oxide catalysts. In the process, ball milling is used to enhance the interaction between solids, promote strong hydrogen bonds and coordination between melamine, metal salts and functional groups such as hydroxyl groups in plant materials, and form a highly active surface, which is conducive to the in-situ generation and uniform dispersion of metal oxides during pyrolysis, and is conducive to nitrogen doping. Through the synergistic effect of doped nitrogen and metal oxides, the obtained nitrogen-doped porous carbon-supported metal oxide catalyst has abundant active sites and good stability. It is applied to catalyze the esterification reaction of rosin, and can achieve efficient esterification of rosin with various polyols such as glycerol and pentaerythritol.
[0018] (2) The preparation process of the present invention is simple, does not require the removal of solvents, does not generate waste liquid, and is easy to scale up for production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The N2 adsorption / desorption isotherms of the nitrogen-doped porous carbon-supported magnesium oxide (Mg-NC) prepared in Example 1 and the porous carbon-supported magnesium oxide (Mg-C) prepared in Comparative Example 3. As can be seen from the figure, the N2 adsorption / desorption isotherms of the two combine the characteristics of type II and type III isotherms, indicating that the prepared materials have a porous structure. Compared with Mg-C, the pore structure of Mg-NC is more developed, which is conducive to the exposure of active sites and mass transfer during the reaction process.
[0020] Figure 2This is the XRD diffraction pattern of nitrogen-doped porous carbon-supported magnesium oxide (Mg-NC) prepared in Example 1. In the figure, the characteristic peaks at 42.6° and 62.1° are attributed to magnesium oxide, and the broad peak near 23.5° is attributed to graphite carbon, indicating that magnesium oxide is successfully supported. DETAILED DESCRIPTION
[0021] A method for preparing nitrogen-doped porous carbon-supported metal oxide comprises the following steps: (1) The plant material, melamine and metal salt were mixed in a mass ratio of 10:1.25:(3.75-37.5), placed in a ball milling jar and placed in a planetary ball mill for ball milling at a speed of 100-800 r / min for 2-10 h; (2) After ball milling, the obtained mixture is taken out, heated to 500-800 °C at a rate of 5-15 °C / min in a nitrogen atmosphere, pyrolyzed and carbonized for 1-4 h, and washed and dried to obtain nitrogen-doped porous carbon-supported metal oxides.
[0022] Wherein, the plant material includes one or more of fir sawdust, hemp stalks and the like.
[0023] The metal salt includes nitrate, acetate or chloride of one or more metals such as magnesium, zinc, cerium, zirconium and the like.
[0024] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0025] Example 1 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0026] (2) The fir sawdust powder obtained in step (1) was placed in a ball mill with melamine and magnesium nitrate hexahydrate in a mass ratio of 10:1.25:7.5, and grinding balls twice the mass of the total material were added, and the mixture was ball milled at 400 r / min for 4 h to obtain a mixed sample.
[0027] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 500°C at a rate of 5°C / min in a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample is naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon-supported magnesium oxide (Mg-NC).
[0028] Weigh 0.3 g of nitrogen-doped porous carbon-supported magnesium oxide (Mg-NC), 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin glycerol ester after filtering the catalyst. After waiting for the product to cool, the acid value of rosin glycerol ester is measured by titration to be 8.42, and the reaction conversion rate is 94.87%.
[0029] Example 2 (1) The hemp stalks were washed thoroughly with deionized water, dried at 105 °C for 24 h, and then crushed to obtain hemp stalk powder.
[0030] (2) The hemp stalk powder obtained in step (1) was placed in a ball mill with melamine and magnesium nitrate hexahydrate in a mass ratio of 10:1.25:7.5, and grinding balls twice the total mass of the materials were added, and the mixture was ball milled at 400 r / min for 4 h to obtain a mixed sample.
[0031] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 500°C at a rate of 5°C / min in a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample is naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon-supported magnesium oxide.
[0032] Weigh 0.3 g of nitrogen-doped porous carbon-supported magnesium oxide, 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin glycerol ester after filtering the catalyst. After waiting for the product to cool, titration determines that the acid value of rosin glycerol ester is 9.82, and the reaction conversion rate is 94.02%.
[0033] Example 3 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0034] (2) The fir sawdust powder obtained in step (1) was placed in a ball mill with melamine and magnesium nitrate hexahydrate in a mass ratio of 10:1.25:7.5, and grinding balls twice the mass of the total material were added, and the mixture was ball milled at 400 r / min for 4 h to obtain a mixed sample.
[0035] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 500°C at a rate of 5°C / min in a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample is naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon-supported magnesium oxide.
[0036] Weigh 0.3 g of the obtained nitrogen-doped porous carbon-supported magnesium oxide, 15 g of rosin, and 1.7 g of pentaerythritol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin pentaerythritol ester after filtering the catalyst. After waiting for the product to cool, titration is performed to determine the acid value of rosin pentaerythritol ester to be 15.43, and the reaction conversion rate is 90.60%.
[0037] Example 4 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0038] (2) The fir sawdust powder obtained in step (1) was placed in a ball mill with melamine and magnesium nitrate hexahydrate in a mass ratio of 10:1.25:7.5, and grinding balls twice the mass of the total material were added, and the mixture was ball milled at 400 r / min for 4 h to obtain a mixed sample.
[0039] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 500°C at a rate of 5°C / min in a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample is naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon-supported magnesium oxide.
[0040] Weigh 0.3 g of nitrogen-doped porous carbon-supported magnesium oxide, 15 g of rosin, and 3.2 g of polyethylene glycol 2000, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin polyethylene glycol ester after filtering the catalyst. After waiting for the product to cool, titration determines that the acid value of the rosin polyethylene glycol ester is 12.43, and the reaction conversion rate is 91.21%.
[0041] Example 5 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0042] (2) The fir sawdust powder obtained in step (1) was placed in a ball mill with melamine and zinc acetate dihydrate in a mass ratio of 10:1.25:7.5, and grinding balls twice the total mass of the materials were added, and the mixture was ball milled at 400 r / min for 4 h to obtain a mixed sample.
[0043] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 800°C at a rate of 5°C / min in a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample is naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon-supported zinc oxide.
[0044] Weigh 0.3 g of the obtained nitrogen-doped porous carbon-supported zinc oxide, 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin glycerol ester after filtering the catalyst. After waiting for the product to cool, the acid value of rosin glycerol ester is measured by titration to be 49.10, and the reaction conversion rate is 70.08%.
[0045] Example 6 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0046] (2) The fir sawdust powder obtained in step (1) was placed in a ball mill with melamine and zirconium oxychloride octahydrate in a mass ratio of 10:1.25:7.5, and grinding balls twice the mass of the total material were added, and the mixture was ball milled at 400 r / min for 4 h to obtain a mixed sample.
[0047] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 800°C at a rate of 5°C / min in a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample is naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon-supported zirconium oxide.
[0048] Weigh 0.3 g of nitrogen-doped porous carbon-supported zirconium oxide, 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin glycerol ester after filtering the catalyst. After waiting for the product to cool, titration determines that the acid value of rosin glycerol ester is 68.73, and the reaction conversion rate is 58.11%.
[0049] Example 7 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0050] (2) The fir sawdust powder obtained in step (1) was placed in a ball mill with melamine and cerium nitrate hexahydrate in a mass ratio of 10:1.25:7.5, and grinding balls twice the total mass of the materials were added, and the mixture was ball milled at 400 r / min for 4 h to obtain a mixed sample.
[0051] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 800°C at a rate of 5°C / min in a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample is naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon-supported cerium oxide.
[0052] Weigh 0.3 g of nitrogen-doped porous carbon-supported cerium oxide, 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin glycerol ester after filtering the catalyst. After waiting for the product to cool, titration determines that the acid value of rosin glycerol ester is 82.76, and the reaction conversion rate is 49.57%.
[0053] Comparative Example 1 Weigh 0.3 g of commercial magnesium oxide, 15 g of rosin, and 3.2 g of glycerol, and add them to a 250 mL three-necked flask; evacuate the air in the three-necked flask, then introduce nitrogen into it, maintain a nitrogen atmosphere, and react at 230 °C for 4 h. After filtering the catalyst, the product rosin glycerol ester is obtained. After waiting for the product to cool, the acid value of rosin glycerol ester is measured by titration to be 89.78, and the reaction conversion rate is 45.30%.
[0054] Comparative Example 2 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0055] (2) Put the fir sawdust powder obtained in step (1) and melamine in a ball mill at a mass ratio of 10:1.25, add grinding balls twice the total mass of the materials, and ball mill at 400 r / min for 4 h to obtain a mixed sample.
[0056] (3) The mixed sample obtained in step (2) was taken out, placed in a muffle furnace, and heated to 500 °C at a rate of 5 °C / min in a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample was naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon (NC).
[0057] Weigh 0.3 g of nitrogen-doped porous carbon (NC), 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin glycerol ester after filtering the catalyst. After waiting for the product to cool, the acid value of rosin glycerol ester is measured by titration to be 72.24, and the reaction conversion rate is 55.98%.
[0058] Comparative Example 3 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0059] (2) The Chinese fir sawdust powder obtained in step (1) and magnesium nitrate hexahydrate were placed in a ball mill at a mass ratio of 10:7.5, and grinding balls twice the total mass of the materials were added, and the mixture was ball milled at 400 r / min for 4 h to obtain a mixed sample.
[0060] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 500°C at a rate of 5°C / min under a nitrogen atmosphere. After being kept at this temperature for 2 h, the mixed sample is naturally cooled, washed with deionized water, and dried to obtain porous carbon-supported magnesium oxide (Mg-C).
[0061] Weigh 0.3 g of porous carbon-supported magnesium oxide (Mg-C), 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, and obtain the product rosin glycerol ester after filtering the catalyst. After waiting for the product to cool, the acid value of the rosin glycerol ester is measured by titration to be 22.44, and the reaction conversion rate is 86.32%.
[0062] Comparative Example 4 (1) Wash the Chinese fir sawdust thoroughly with deionized water, dry it at 105 °C for 24 h, and then grind it to obtain Chinese fir sawdust powder.
[0063] (2) The fir sawdust powder obtained in step (1) is directly mixed with melamine and magnesium nitrate hexahydrate in a mass ratio of 10:1.25:7.5.
[0064] (3) The mixed sample obtained in step (2) is taken out, placed in a muffle furnace, and heated to 500°C at a rate of 5°C / min under a nitrogen atmosphere. After being kept at this temperature for 2 h, it is naturally cooled, washed with deionized water, and dried to obtain nitrogen-doped porous carbon-supported magnesium oxide (U-Mg-NC) prepared without ball milling-assisted strategy.
[0065] Weigh 0.3 g of the above-mentioned nitrogen-doped porous carbon-supported magnesium oxide (U-Mg-NC), 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; evacuate the air in the three-necked flask, and then introduce nitrogen into it to maintain a nitrogen atmosphere. React at 230 °C for 4 h, filter the catalyst to obtain the product rosin glycerol ester, wait for the product to cool, and titrate to determine the acid value of rosin glycerol ester to be 49.80, and the reaction conversion rate is 69.66%.
[0066] Recycling experiment The recycling performance of nitrogen-doped porous carbon-supported magnesium oxide (Mg-NC) prepared in Example 1, porous carbon-supported magnesium oxide (Mg-C) prepared in Comparative Example 3, and nitrogen-doped porous carbon-supported magnesium oxide (U-Mg-NC) prepared without ball milling-assisted strategy in Comparative Example 4 was investigated. The specific operation is to weigh 0.3 g of sample, 15 g of rosin, and 3.2 g of glycerol, and add them into a 250 mL three-necked flask; the air in the three-necked flask is evacuated, and then nitrogen is introduced into it to maintain a nitrogen atmosphere, and the reaction is carried out at 230°C for 4 h. The catalyst is filtered and recycled for the above reaction. After three cycles of experiments, the product rosin glycerol ester is cooled, and its acid value and reaction conversion rate are titrated to test.
[0067] The results show that after three cycles of experiments, the acid value of the product rosin glycerol ester prepared with Mg-C as the catalyst increased significantly, and the conversion rate decreased significantly, which were 70.14 and 57.26% respectively; the acid value of the product rosin glycerol ester prepared with U-Mg-NC as the catalyst increased significantly, and the conversion rate decreased significantly, which were 105.21 and 35.90% respectively; while the acid value of the product rosin glycerol ester prepared with Mg-NC as the catalyst increased slightly, and the conversion rate decreased slightly, which were 19.64 and 88.03% respectively; it can be seen that the ball milling-assisted strategy combined with nitrogen doping significantly improved the stability of the catalyst.
[0068] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A method for preparing nitrogen-doped porous carbon-supported metal oxide, characterized in that: The following steps are involved: (1) ball-milling and mixing plant materials, melamine and metal salt; (2) The mixture obtained in step (1) is subjected to pyrolysis and carbonization in a nitrogen atmosphere to obtain the nitrogen-doped porous carbon-supported metal oxide.
2. The method for preparing nitrogen-doped porous carbon-supported metal oxide according to claim 1, characterized in that: The mass ratio of the plant material, melamine and metal salt used in step (1) is 10:1.25:(3.75~37.5).
3. The method for preparing nitrogen-doped porous carbon-supported metal oxide according to claim 1 or 2, characterized in that: The plant material includes one or more of fir wood chips and hemp stalks.
4. The method for preparing nitrogen-doped porous carbon-supported metal oxide according to claim 1 or 2, characterized in that: The metal salt includes nitrate, acetate or chloride of one or more of magnesium, zinc, cerium and zirconium.
5. The method for preparing nitrogen-doped porous carbon-supported metal oxide according to claim 1, characterized in that: The ball milling speed in step (1) is 100-800 r / min, and the time is 2-10 h.
6. The method for preparing nitrogen-doped porous carbon-supported metal oxide according to claim 1, characterized in that: The heating rate of the pyrolysis carbonization in step (2) is 5-15 °C / min, the temperature is 500-800 °C, and the time is 1-4 h.
7. Use of a nitrogen-doped porous carbon-supported metal oxide prepared by the method of claim 1 in catalyzing esterification of rosin.
8. The use according to claim 7, characterized in that: The nitrogen-doped porous carbon-supported metal oxide is used as a catalyst to catalyze the esterification reaction of rosin and polyol to obtain the corresponding rosin ester.
9. The use according to claim 8, characterized in that: The polyol includes one or more of glycerol, ethylene glycol, polyethylene glycol, and pentaerythritol.
10. The use according to claim 8, characterized in that The mass ratio of rosin to polyol used is 15:(1.5-4.6); the temperature of the esterification reaction is 210-250°C, and the time is 2-6 hours.
Citation Information
Patent Citations
Method for preparing metal-carbon composite catalytic material and its application
CN109718822A
Nitrogen-doped porous carbon-supported bimetallic catalyst and preparation method and application thereof
CN109999880A
Preparation method of special nitrogen-doped molded active carbon for catalyst carrier
CN111186837A
Preparation method of nitrogen and / or sulfur modified three-dimensional porous carbon material
CN114804096A
Preparation method and application of nitrogen-doped porous carbon supported iron catalytic material
CN116920844A
